Progesterone in implantation and early pregnancy - N A Tatarova; M S Airapetyan (IP Berlin A.V., 2014)
The article highlights the issues concerning implantation and endometrial decidualization. Mechanism of spontaneous abortion. Assessed is the need for progestogens in the treatment and prevention of recurrent miscarriage and threatened abortion. The article provides an overview of progesterone drugs used in routine practice by obstetricians.